Pengabdian KKM 04 ex.IAIN Persemakmuran Berupa Penerapan Digital Marketing dalam Upaya Peningkatan Pendapatan UMKM Jago Kembar di Desa Gading Kembar - Fattah, Mustamin; Rosdiana, Siti; Fardan Labibi, Muchammad Ali; Jannah, Firdana Miktahul (TAFANI: Jurnal Pengabdian Masyarakat, 2023)
Service is part of the pillars of the Tri Dharma of Higher Education. As is well known, service that is usually carried out by students from an institution is an activity that does not expect rewards but the aim is purely to help the community. The form of service carried out at KKM 04 Persemakmuran ex Sunan Ampel is counseling on the application of digital marketing in an effort to increase the income of MSMEs. This research uses descriptive qualitative methods with purposive data collection techniques, namely collecting primary data and secondary data. The results of this study show that the Jago Kembar Cassava Chips MSME players have never marketed their products through digital marketing, therefore the researchers conducted counseling and provided suggestions according to what was needed by the MSME business actors. The conclusion in this study is that now MSME business actors can take advantage of the use of social media in marketing their products, as well as the hopes of KKM 04 ex.IAIN Persemakmuran Gading Kembar students so that the income of the Jago Kembar Cassava Chips MSME can increase when digital marketing is implemented.